A LITERATURE REVIEW: THE RELATIONSHIP BETWEEN COMPLIANCE AND THERAPY OUTCOMES FOR HYPERTENSIVE PATIENTS AT THE PUBLIC HEALTH CENTER - Paradillah, Sarah; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Hypertension, also recognized as elevated blood pressure, denotes an elevation in systolic blood pressure beyond the standard threshold. Hypertension is characterized as elevated blood pressure, indicated by a systolic pressure exceeding 140 mmHg and a diastolic pressure surpassing 90 mmHg. The level of patient compliance in taking medication influences the therapy outcomes for hypertensive patients. The patient's compliance in using medication influences the success of treatment therapy. Non-adherence to medication among hypertensive patients can lead to significant adverse outcomes, including the development of complications. Poor compliance with medication can result in blood pressure not showing significant improvement, resulting in poor quality of life. This study aimed to review articles regarding the relationship between compliance and therapy outcomes for hypertensive patients. This research employed a systematic literature review methodology. The searches for this review article were Google Scholar, Research Gate, Pubmed, and Portal Garuda using the selected keywords, namely Hypertension, Therapy Outcomes, and Compliance. The results obtained from 5 literature studies showed that the relationship between compliance to taking medication and therapy outcomes based on gender, age, education level, occupation, and quality of life influenced compliance to antihypertensive therapy. In summary, a substantial correlation exists between adherence to antihypertensive medication and therapeutic outcomes among hypertensive patients, with the average result yielding a p-value of 0.000 (p < 0.05). Based on the results of the review of articles that have been obtained, suggestions that can be given are to examine the relationship between compliance and therapy outcomes of hypertension patient with comorbidities. Keywords: Hypertension, Therapy Outcome, Compliance